Productivity of Boran cattle and their Friesian crosses at Abernossa ranch, rift valley of Ethiopia. II. Growth performance - Banjaw, K.; Haile-Mariam, M. (Springer, 1994)
Birth (4,197) and weaning (2,441) weight data on Boran, F1 Boran Friesian and three quarter Friesian calves as well as adjusted one-year (390), 2 year (177) and 3-year (364) weights on Boran cattle were analysed to estimate the influence of genetic and environmental factors. Boran, F1 and three quarter calves weighed 25.2, 25.4 and 27.7 kg at birth and 157.5, 176.7 and 179.9 kg at weaning, respectively. All factors included in the analysis and their interaction had significant effects on both traits with the exception of the effect of season on birth and its interaction with breed group on birth weight. Weight of Boran cattle at one-, 2- and 3-years of age were 179, 269 and 338 kg, respectively. Heritability values calculated on the basis of paternal half-sibs were 0.32, 0.24, 0.48, 0.29 and 0.24 for birth, weaning, one-year, 2-year and 3-year weights, respectively. The study indicated that F1 crosses were 12.2% heavier at weaning than Boran calves. Of the environmental factors considered, year of birth was found to be the major source of variation mainly due to variation in the amount of rainfall between years.